Influence of internal social capital and external social capital on product innovation - Sang, Phung Khac; Hoan, Nguyen; Huy, Pham Van; Phuong, Mai Quynh; Huong, Nguyen Thuy (Edelweiss Applied Science and Technology, 2025)
Product innovation plays an important role in enhancing the competitiveness of enterprises, creating new products and services, and better meeting the needs of customers and the market, thereby increasing market share and revenue. Product innovation helps firms maintain market appeal, meet customer needs, and create a competitive advantage. The purpose of this study is to determine whether internal social capital and external social capital have a positive impact on product innovation. This study uses a quantitative research design supported by SPSS software. The population in this study consisted of respondents from plastic and packaging firms in Vietnam, while the sample was obtained from 275 respondents, including office staff, sales staff, accountants, etc., from plastic and packaging firms. The sampling technique used was purposive sampling. The data analysis techniques included reliability analysis of scales through Cronbach’s alpha coefficient, exploratory factor analysis (EFA), correlation analysis, and regression models. The overall research results show that internal social capital and external social capital positively impact product innovation. These results are also supported by the consistency of the responses to each question item for the independent and dependent variables. Based on the research findings, we propose some recommendations to enhance product innovation in plastic and packaging enterprises, thereby contributing to improved business performance.